2008
DOI: 10.1007/s00284-008-9097-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Predominant Lactic Acid Bacteria Associated with Cocoa Fermentation in Nigeria

Abstract: The fermentation of cocoa relies on a complex succession of bacteria and filamentous fungi, all of which can have an impact on cocoa flavor. So far, few investigations have focused on the diversity of lactic acid bacteria involved in cocoa fermentation, and many earlier investigations did not rely on polyphasic taxonomical approaches, which take both phenotypic and genotypic characterization techniques into account. In our study, we characterized predominant lactic acid bacteria from cocoa fermentations in Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 14 publications
6
54
0
1
Order By: Relevance
“…Samples of 500 g were collected according to a fixed time schedule, namely, at the start of fermentation (time zero, fresh cocoa beans) and after 6,12,18,24,30,36,42,48,54,60,66,72,84, and 96 h of fermentation. Additional samples were taken immediately after transfer and mixing during the box fermentations and after 120 h in the case of prolonged fermentations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of 500 g were collected according to a fixed time schedule, namely, at the start of fermentation (time zero, fresh cocoa beans) and after 6,12,18,24,30,36,42,48,54,60,66,72,84, and 96 h of fermentation. Additional samples were taken immediately after transfer and mixing during the box fermentations and after 120 h in the case of prolonged fermentations.…”
Section: Methodsmentioning
confidence: 99%
“…Additional data on cocoa bean fermentation processes performed in Indonesia, the Dominican Republic, and Nigeria, albeit partially carried out multiphasically, have become available (3,30,31). Despite the reputation of Ecuadorian cocoa regarding its fine flavor, little is known about the microbial communities active in Ecuadorian cocoa bean fermentations.…”
mentioning
confidence: 99%
“…As the pulp drains away, air penetrates into the fermenting mass, which creates ideal conditions for the growth of bacteria. Microaerophilic, acid-tolerant, and ethanol-tolerant lactic acid bacteria (LAB), in particular, Lactobacillus plantarum and Lactobacillus fermentum, first dominate the fermentation (1,4,11,12,19). Glucose, fructose, and citric acid are converted into acetic acid, lactic acid, and/or mannitol, resulting in a slight increase in the pH of the pulp (4).…”
mentioning
confidence: 99%
“…On the other hand, produced by lactic bacteria is not desirable due to the negative impact on the cocoa beans [2]. [47] are demonstrated that high level of lactic acid in cocoa beans fermenting mass may allow enhanced growth of Acetobacter genus which is able to metabolize lactic acid. Consequently, predominance of homofermentative forms in Agnéby-Tiassa cocoa fermentation may constitute alternative asset considering the important role of AAB in fermentative process and on the quality of end products.…”
Section: American Journal Of Bioscience 2015;mentioning
confidence: 99%